PENDAMPINGAN KEGIATAN EKSRAKURIKULER KIR DALAM UPAYA MENINGKATKAN KUALITAS SEKOLAH SMA DWIJENDRA DENPASAR - Komang Dharmawan; Y. Ramona; N. N. Rupiasih; I G. A. Widagda (Buletin Udayana Mengabdi, 2020)
Youth Scientific Work (KIR) basically aims to trigger curiosity about natural phenomena related to science and technology. KIR can also increase the ability to think critically about natural phenomena and increase creativity that fosters creative ability and critical thinking. The purpose of this assistance is to introduce research methods for groups of teachers so students get better quality coaching. The mentoring method applied is In-House-Training, which is the implementation of mentoring at the relevant school. In this assistance 4 scientific works have been produced by high school students of Dwijendra Denpasar who are ready to be presented in KIR competitions both regionally and nationally.